Dampak Perceived Organizational Support Terhadap Organizational Citizenship Behavior Dimediasi Komitmen Organisasi di PTPN IV - Mukhlis Hutabarat, Afwa (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the impact of Perceived Organizational Support (POS) on Organizational Citizenship Behavior (OCB) mediated by organizational commitment. POS represents employees' perception of the support provided by the organization regarding their well-being and contributions. OCB refers to extra-role behaviors that enhance organizational effectiveness. This study employed Partial Least Squares (PLS) as the analysis method, with a sample of 197 employees from PT Perkebunan Nusantara IV Medan. The results indicate that POS has a significant positive effect on OCB, both directly and through organizational commitment as a mediator. Organizational commitment plays a crucial role in strengthening the relationship between POS and OCB. Employees who perceive strong organizational support tend to develop higher organizational commitment, which in turn fosters higher levels of OCB. Factors such as recognition, work environment, and employee well-being contribute to a positive perception of organizational support. The implications of this study highlight the importance of organizations investing in employee welfare, creating a supportive work environment, and implementing policies that recognize and reward high-performing employees. By doing so, organizations can foster greater employee loyalty and extra-role contributions, ultimately driving overall organizational success. Future research could explore additional variables that may further mediate or moderate these relationships.